Claiming appearances in Jacques Rancière’s work - Hannah Estrella (GoAcademica Research & Publishing, 2021)
The present article aims to analyze the notion of appearance in Jacques Rancière's philosophical work, with a view to delineating a digressive line of a long tradition that insists on affirming the power of thought and truth against the inconsistency of appearances. In this sense, an attempt is made to argue the potential that appearances have in the construction of new imaginaries and in the creation of other forms of common sense.